An Azide‐Substituted Triarylborane: A Key Compound for the Facile Synthesis of Fluorescent Triarylboranes Bearing Triazole Moieties as Connectable π‐Conjugated System Linkages. Issue 35 (9th September 2019) - Yoshino, Junro; Konishi, Shota; Kanno, Ryosei; Hayashi, Naoto; Higuchi, Hiroyuki
Abstract : Tris(4‐azido‐2, 6‐dimethylphenyl)borane was readily synthesized from an amino‐substituted triarylborane using tert ‐butyl nitrite and trimethylsilylazide. This compound can easily be converted into triarylboranes bearing various π‐conjugated moieties with triazole ring π‐linkers through a Huisgen cycloaddition. UV/Vis absorption spectra and DFT calculations suggested that constructing a triazole linker successfully extended the π‐conjugated system of triarylboranes. Triarylboranes obtained using this method maintained their fluorescent nature. In particular, the triarylborane linking N, N ‐dimethylaminophenyl groups with triazole rings exhibited notable visible solvatofluorochromism and fluorescence color change upon addition of a fluoride anion. Abstract : Tris(4‐azido‐2, 6‐dimethylphenyl)borane was synthesized and easily converted into fluorescent triarylboranes bearing various π‐conjugated moieties with triazole ring π‐linkers via a Huisgen cycloaddition. The triarylborane linking N, N ‐dimethylaminophenyl groups with triazole rings exhibited notable visible solvatofluorochromism and fluorescence color change upon addition of a fluoride anion.